Pengaruh Manajemen Laba, Koneksi Politik, Kepemilikan Asing terhadap Kinerja Perusahaan - Shilvia Aristiowati; Mochammad Ilyas Junjunan; Ashari Lintang Yudhanti; Selvia Eka Aristantia (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2022)
This study aims to analyze the effect of earnings management, political connection, and foreign ownership on company performance This test was carried out on 92 consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. The data were processed using Stata with multiple regression analysis method equipped with the Chow and Hausman specification tests. The results showed that earnings management had a positive effect on company performance, while political connection and foreign ownership had no significant effect on company performance. This finding indicates that the company does not communicate well information related to the company's performance. Therefore, earnings management is often used as an effort to improve company performance. Furthermore, this study also indicates that political connection and foreign ownership are not an important mechanism that can improve company performance. This research adds to the study of company performance and has implications for corporate management and policy makers.